Spoken Language Development and the Challenge of Skill Integration - Noiray, Aude; Popescu, Anisia; Killmer, Helene; Rubertus, Elina; Krüger, Stella; Hintermeier, Lisa (Frontiers in Psychology, 2019)
The development of phonological awareness, the knowledge of the structural combinatoriality of a language, has been widely investigated in relation to reading (dis)ability across languages. However, the extent to which knowledge of phonemic units may interact with spoken language organization in (transparent) alphabetical languages, has hardly been investigated. The present study examined whether phonemic awareness correlates with coarticulation degree, commonly used as a metric for estimating the size of children´s production units. A speech production task was designed to test for developmental differences in intra-syllabic coarticulation degree in 41 German children from 4 to 7 years of age. The technique of ultrasound imaging allowed for comparing the articulatory foundations of children´s coarticulatory patterns. Four behavioral tasks assessing various levels of phonological awareness from large to small units and expressive vocabulary were also administered. Generalized additive modelling revealed strong interactions between children´s vocabulary and phonological awareness with coarticulatory patterns. Greater knowledge of sub-lexical units was associated with lower intra-syllabic coarticulation degree and greater differentiation of articulatory gestures for individual segments. This interaction was mostly nonlinear: an increase in children’s phonological proficiency was not systematically associated with an equivalent change in coarticulation degree. Similar findings were drawn between vocabulary and coarticulatory patterns. Overall, results suggest that the process of developing spoken language fluency involves dynamical interactions between cognitive and speech motor domains. Arguments for an integrated-interactive approach to skill development are discussed.